Sulfur metabolism in higher plants : fundamental, environmental and agricultural aspects - De Kok, L. J.; Hawkesford, Malcolm J.; Haneklaus, Silvia H.; Schnug, Ewald (Proceedings of the International Plant Sulfur Workshop., 2017)
"This proceedings volume contains a selection of invited and contributed papers of the 10th International Workshop on Sulfur Metabolism in Plants, which was held in Goslar, Germany September 1-4, 2015. The focus of this workshop was on the fundamental, environmental and agricultural aspects of sulfur in plants, and presents an overview of the progress in the research developments in this field in the 28 years since the first of these workshops. The volume covers various aspects of the regulation of the uptake and assimilation of sulfate in plants from a molecular to a whole plant level with an emphasis on the significance of sulfur metabolism in plant responses to stress and in food security."--Provided by publisher.